Training distribution in rowers: a case study of an olympic gold medalist - Wang, Y. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Against the backdrop of the postponement of the Tokyo Olympic Games, the Chinese National Rowing Federation made training measures and load adjustments for the competition year of the Tokyo Olympic cycle. As a result of the load design, Chinese elite rowers won a gold medal and two bronze medals at these Olympic Games. The purpose of this paper is to analyze the overall load differences between the two years of preparation for the Olympic Games using the two-year training cycle of the bronze medal-winning Chinese women rowers as an example METHODS: Methods: Subject Table 1*Elite rowers personal information Number Year High body weight*kg* X1 24 179 74 X2 30 187 78.4 X3 27 188 80.6 X4 29 181 85 X5 28 181 85 X6 29 181 76 X7 27 180 81 X8 29 185 78.5 Eight female former and current China elite rowers (Table 1). All athletes had won a least one individual Olympic or World Championship senior gold medal during their career. Design The training schedule was adjusted to September 2019-August 2020 for the Olympic qualifiers and September 2020-August 2021 for the Olympic competition. During this cycle, the researchers have systematically and accurately recorded the rowers training routines. The training consisted of training time on the water, dynamometer *Concept2* training, strength training, cross training and other training. RESULTS: For the womens eight-man single scull, the total load for the two competition years was 1243.26 hours and 988.37 hours, respectively. Water training was reduced by 20.18 hours, Concept2 training time was decreased by 98.32 hours, strength training was accelerated by 141.40 hours, cross training was reduced by 3.08 hours, another training was increased by 42.82 hours, stretch regeneration was decreased by 34 hours, and overall training time was reduced by 254.89 hours, according to a comparison of the two competition years. CONCLUSION: This case study is the first study in Chinese rowing to adjust the load for the summer Olympic Games competition year, and the total load for the two competition years supports the previous conclusion that elite endurance athletes train up to 1000 hours per year and are not significantly altered by changes in Olympic competition time limits.